Inter-Worldview Education and the Re-Production of Good Religion - Marianne Moyaert (MDPI AG, 2018)
In this article, I focus on the increasing interest taken by European political and educational policy makers in inter-worldview education. My article has two parts. The first part consists of a document analysis of pivotal European publications on this and related issues. In the second and more critical part of this article, I make explicit my concerns about these European pleas for inter-worldview education. The main criticism that I present below is that the European policy on inter-worldview dialogue views the problem of intolerance too much as an individual problem that can and must be dealt with pedagogically, without recognizing that intolerance is just as much a structural socio-political problem. Important European policy documents, to be examined in the first part of this article, do not discuss how the way our societies are structured results in a sustenance of inequalities and in the marginalization of certain groups of people. At no point does these documents link inter-worldview education to the need “to examine the ideologies and structures of society critically,” as a consequence the plea for dialogue loses some of its critical and transforming potential.